VALUATION OF INTELLECTUAL PROPERTY ON NFT TRANSACTION FOR NFT PLATFORM IN INDONESIAN PERSPECTIVES - Novianty Muchtar, Helitha; Risang Ayu, Miranda; Amirulloh, Muhamad (Transnational Business Law Journal, 2022)
Recently, NFT enable its owner to sell and buy intellectual properties. The research result shows that an NFT transaction process – such as in the sale and purchase of intellectual property-requires a determined price valuation. The authors consider that it is necessary to determine a clear valuation to predict the exact price of the intellectual property digitally transacted on NFT. The price database on NFT can be used to determine the price by first collecting the NFT and the price database can also calculate the value of the NFT in the future.